Comparison of Methods Used for Ultrasonic Examinations of IMT in the Wall of the Carotid Artery Model - TRAWIŃSKI, Zbigniew; WÓJCIK, Janusz (Archives of Acoustics, 2008)
The aim of this paper is to compare the results of examinations of the intima-media thickness (IMT) in the wall of the carotid artery model by means of zero-crossing and correlation methods. The research was carried out on the elastic artery model (a pipe made of latex), with the internal diameter of 3, 5 and 8 mm and the wall thickness of 0.75, 1.25 and 2 mm. A numerical solver was created for the purpose of calculating the fields of ultrasonic beams and scattered fields under different boundary conditions, different angles and transversal displacements of ultrasonic beams in respect of the position of the arterial wall. A VED ultrasonic apparatus was used during the investigations. The frequency of the transmitted ultrasound was 6.75 MHz. The numerical solver was used for the creation of ultrasonic RF reference signals. A good conformity was obtained between changing the numerical reference of the IMT and the results of determining the IMT by both the zero-crossing method and the correlation method.